The challenge of Mediterranean sclerophyllous vegetation under climate change: From acclimation to adaptation - Bussotti, Filippo; Ferrini, Francesco; Pollastrini, Martina; Fini, Alessio (Environmental and Experimental Botany, 2014)
Forecasting models for climate change in southern Europe differ from those proposed for central and northern regions mainly with regard to precipitation. In fact, a strong reduction in average rainfall, mainly caused by decrease frequency of rainy events, is believe to occur in the Mediterranean basin in the forthcoming hundred years. Increased frequency of drought events will be paralleled and exacerbated by warming. Differently from areas where plant growth is limited by sub-optimal temperature (i.e. boreal and most temperate forests) and where warming has been reported to increase carbon assimilation and growth, plants growing in the Mediterranean basin are currently near their temperature optimum, and warming may contribute (e.g. with drought) to impair photosynthesis and depress growth and survival. Rising atmospheric CO2 has been found to increase growth, photosynthesis water use efficiency, and may partially alleviate the deleterious effects of warming and drought. However, in areas where severe and prolonged drought episodes occur, severe photoinhibition and metabolic limitation to photosynthesis may prevent Mediterranean sclerophylls to take advantage of higher atmospheric CO2, and may slow down recovery after the end of the dry season. The most sensitive forest types consist in tree species which are, in the Mediterranean basin, at the southernmost limit of their distribution range. In contrast, thermophilous trees are expected to have a greater diffusion both in southern and central Europe, as winter cold stress will be reduced by warming. Yet due to great variability of ecological features, the alleged substitution of tree species can follow a natural pattern from south to north and from low to high altitudes, without considering obstacles deriving from urbanization. For these reasons, research on the performance and ecologic plasticity of different genotypes, on species selection, and on planting and management techniques can have strategic importance for adaptive forest management.
Keywords: Drought stress; Global warming; Ozone; photosynthesis; UV radiation; Vegetation shift

Functional traits and adaptive capacity of European forests to climate change - Bussotti, Filippo; Pollastrini, Martina; Holland, Vera; Brüggemann, Wolfgang (Environmental and Experimental Botany, 2014)
Increasing temperatures and drought risks through climate change are expected to have several consequences for European forests. Adaptive strategies may include: (i) persistence of the current forest types, thanks to the acclimatization to local conditions and to phenotypic plasticity of the populations; (ii) evolution, or local adaptation, i.e., change in genotype (frequencies) within the same species due to environmental pressure. It is favored by large within population diversity and (when possible) gene flow among populations; (iii) migration and substitution of species; and (iv) extinction of populations with low ecological plasticity, especially at the edges of their distribution or in the case of isolated (relict) populations. Because of the economic and ecological relevance of forests, it is of fundamental importance to apply appropriate forest management to make forests able to cope with the new environmental conditions. This may include changes in the composition and structure of forest stands, selection of adapted provenances of the most important European tree species or, if this is regarded as insufficient, assisted migration (i.e., the use of species suitable for the future climatic conditions) and, alternatively, substitution of native with non native species. The intraspecific (genetic and phenotypic) variability at a given site has been proven to be often higher than the variability among sites. Species with a large distribution range are supposed to have a wide variety of genotypes, allowing them to be adapted to different environmental conditions. Genetic variability and phenotypic plasticity are the key factors for the identification of useful tree genotypes for future forestation programs. Adaptation to drought, i.e., the probably most important future abiotic risk factor for forestry, can be reflected in variation of key functional traits (FT), at morphological, physiological and phenological level. FT utilized to screen for adapted genotypes in common gardens and provenance trials include growth, survival, leaf flushing and senescence, foliar features as leaf mass per area and nitrogen content, water use efficiency (e.g., estimated by analysis of the stable carbon isotopes, d13C) chlorophyll content, photosystem II functioning, and photosynthetic capacity under water shortage. Current modeled simulation of future forest distribution suggests the expansion of forests at the highest latitudes and altitudes, alongside with a reduction in the hottest and driest Mediterranean regions of South Europe. The general expectations, however, may be disproved especially at a regional level, by factors unexpected or not well known, such as possible extreme climatic events and increased roles of parasites/diseases (with negative effects), or high capacity of forest persistence or adaptation (with positive effects). Natural migration and species substitution can be hampered by co-factors of climate change, such as forest fragmentation and increased frequency and intensity of forest fires.
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Adaptation; Extinction; functional traits; Local evolution; migration; Phenotypic plasticity; Phenotyping; provenances

Ozone stress in woody plants assessed with chlorophyll a fluorescence. A critical reassessment of existing data - Bussotti, Filippo; Desotgiu, Rosanna; Cascio, Chiara; Pollastrini, Martina; Gravano, Elisabetta; Gerosa, Giacomo; Marzuoli, Riccardo; Nali, Cristina; Lorenzini, Giacomo; Salvatori, Elisabetta; Manes, Fausto; Schaub, Marcus; et al. (Environmental and Experimental Botany, 2011)
This paper proposes an overall reassessment of results from ﬂuorescence transient (FT) and modulated ﬂuorescence (MF) analysis on tree species subjected to treatment with ozone. Findings from literature and open-top chamber experiments were used in this review, in order to identify damage mechanisms and repair/avoidance strategies. Main results are summarised below. (i) The most widely used parameter to assess the response to ozone treatment was the quantum yield of primary photochemistry in the dark-adapted state (ϕPo, or FV/FM). This parameter proved to be very stable in stress and control conditions. Ozone-induced stress – and the related loss of photosynthetic efﬁciency and performance – was characterized by the change occurring in all parameters connected with the controlled dissipation: reduction of FM, FV/FM, RC/CS0 (in the ﬂuorescence transient analysis) and NPQ (in theMF analysis). This can be considered as a down-regulationmechanism aimed at lowering the electron supply as a consequence of a reduced demand from the Calvin cycle. (ii) The FT analysis revealed a change in the I–P region shape, indicating that events beyond PSI are affected. These events include a lesser density of PSI itself and the compromised ability of the end acceptors of electrons (ferredoxine, NADP + ) and RuBP to manage effectively the ﬂux of electrons. This behaviour may create an imbalance between electrons sent by the electron transport chain and those reaching the acceptors beyond PSI. Free electrons (those coming from PSI, but that do not reach the end acceptors) can activate the oxygen from fundamental to excited status, with production of ROS (Reactive Oxygen Species), thus inducing photo-oxidation processes of the cellular content. (iii) In many cases a temporarily enhanced efﬁciency of electron trapping and transport (expressed by the parameters FV/FM, ET/TR, PIABS, pQ) in PSII system has been observed. That efﬁciency has been connected to the triggering of repair processes, but when it is connected to a reduced end acceptor capacity in combination with reduced Calvin cycle energy demand lead to over-excitation of the photosynthetic apparatus and initiates response towards visible foliar injury. (iv) The behaviour of F0 can help us distinguish between different response strategies. The increase of F0 observed in some ozone-treated plant species is considered an expression of irreversible damage in PSII, whereas lowered values of this parameter may indicate the activation of PSII in the cells surrounding the damaged one, as part of a compensative process. Future directions for the research in this ﬁeld concern: (i) the possibility to combine ﬂuorescence parameters with carbon assimilation and growth to support the study on critical levels and (ii) the analysis of the events concerning the activity of PSI and the events leading to the ﬁxation of CO2, by using innovative technologies
The following values have no corresponding Zotero field: publisher: Elsevier B.V.
Keywords: Chlorophyll a fluorescence; OKJIP transient; Open top chambers; Ozone stress; Performance index; Quantum yield efficiency; Reaction centres; Visible foliar symptoms